Analyzing if and how international organizations contribute to the sustainable development goals: Combining power and behavior. (22nd November 2016) - Cormier, Ben
Summary: Can International Organizations (IOs) such as the World Bank, United Nations, and International Labor Organization contribute to the Sustainable Development Goals (SDGs)? This article argues that this is best analyzed by simultaneously considering two sets of factors: the international political constraints external to IOs and the organizational processes and structures internal to IOs. More specifically, this article suggests that such analyses can take place by combining scholarship on International Relations (IR) and Organizational Behavior (OB). The article defines international power, outlines various constraints on IO autonomy, and suggests that OB and IR are well positioned to jointly improve the study of IO employment practices, organizational structures, bureaucratic politics, and inter‐organizational effects. The core aim is to provide justification and material for combining IR and OB in further research on IOs.